High-definition brain stimulation targeting separate regions leads to differential word retrieval outcomes in patients with primary progressive aphasia: a pilot study - Dugas, Christine Sofka; Chiang, Hsueh-Sheng; Devora, Paulina; Lucas-Mendoza, Katelyn; Abasi, Christine; Adhikari, Ashna; Nguyen, Trung; Frolov, Alexander; Kelley, Brendan J.; LoBue, Christian; Mudar, Raksha A.; Hart, John (Frontiers in Neurology, 2025)
BackgroundWord retrieval deficits are the most prominent symptoms reported in primary progressive aphasia (PPA) and related syndromes. Current treatments, such as speech and language therapy, have shown limited success, highlighting the need for alternative non-pharmacological interventions with high-definition transcranial direct current stimulation (HD-tDCS) emerging as a promising tool.ObjectiveThis study aimed to evaluate the effects of HD-tDCS on word retrieval function in individuals with PPA by comparing two stimulation sites: the pre-supplementary motor area (pre-SMA) and the left inferior frontal gyrus (LIFG), and to assess the relative benefits of each site.MethodsEight individuals with PPA underwent 10 sessions of open-label HD-tDCS targeting either the LIFG (n = 4) or pre-SMA (n = 4). Word retrieval was assessed at baseline, immediately post-stimulation, and at 8-week follow-up. Electrophysiological measures, including event-related potentials during a non-verbal Go-NoGo task, were also collected to explore neural mechanisms.ResultsLIFG stimulation yielded statistically significant improvements in phonemic fluency at immediate post testing compared to baseline, with 25–50% showing clinically meaningful improvement. Clinically meaningful improvement was observed in category fluency in 25–50% of the patients receiving stimulation at either site. Lastly, electrophysiological measures indicated HD-tDCS targeting LIFG differentially modulated event-related potential effects during non-verbal Go-NoGo tasks.ConclusionThis research provides preliminary evidence supporting the use of both traditional (LIFG) and alternative (pre-SMA) stimulation sites for treating word retrieval deficits in individuals with PPA. The findings also suggest potential neural mechanisms of HD-tDCS intervention, which can inform future designs of non-invasive brain stimulation for cognitive symptoms in PPA.Clinical trial registrationClinicaltrials.gov, identifier NCT05368350.